The Effectiveness Of Information Systems In Improving Human Resource Management In Jordanian Banking Sector - Md Faruk, Abdullah; Arafat Alshaikh, Theeb (2018)
There is an increasing need for analysing the effectiveness of information systems in human resource management in the banking industry due to the competitive environment under which the banks operate. In the current globalization era, effective application of human resource management information system in the banks is necessary. Therefore, this paper focuses on reviewing the most relevant studies on the effectiveness of information systems in human resource management in Jordanian banking sector. Studies in the area of information systems and human resource management are reviewed to know whether the information systems in Jordanian baking sector are effective. This paper provides better understanding of the role of information systems in improving the human resource management. The paper discusses the relationship between information system and human resource management in light of the global competition for the effective and competent human resources to perform managerial activities.